Volume and Frequency of Transactions that Influence Share Prices are Mediated by Financial Performance and Moderated by Dividend Policy - Bambang Susanto; Rima Dwijayanty; Sukadwilinda Sukadwilinda (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
One of the benchmarks for a country's progress is the existence of the Capital Market. The capital market is a gathering place for public companies operating in both primary and secondary markets. The secondary market in the capital market is a preference for people and organizations to invest. Share prices are a consideration for investors in determining investment decisions. The online trading system in the capital market is considered an efficient step and makes it easier to accelerate transactions, both buying and selling. The impact of transaction speed allows transaction volume and frequency to increase. The increase in transaction volume and frequency can only be seen in terms of technical factors, but fundamental factors in investing in the capital market also need to be considered. In this study, the researcher tried to include financial performance as well as a moderating variable which is proxied by dividend policy which is thought to influence stock prices. The results of research model 1 show an R-squared value of 0.487204. This shows that transaction volume, transaction frequency and DPR contributed 48.72% to PBV, while the remaining 51.28% was the contribution of other variables besides the independent variables studied. Meanwhile, Model 2 shows an R-squared value of 0.956943. This shows that PBV, Transaction Volume, Transaction Frequency and DPR contribute to SP amounting to 95.69% while the remaining 4.31% is the contribution of other variables besides the independent variables studied.